A Journey with Platelet P-Selectin: The Molecular Basis of Granule Secretion, Signalling and Cell Adhesion - Furie, Bruce; Furie, Barbara C.; Flaumenhaft, Robert (Thrombosis and Haemostasis, 2001)
P-selectin is a transmembrane protein that resides within the alpha granule membrane of unstimulated platelets. The “extracellular” domains face into the lumen of the granule and the cytoplasmic tail extends into the platelet cytoplasm. Upon platelet stimulation, P-selectin is phosphorylated and translocated to the plasma membrane via a secretory pathway. P-selectin in the plasma membrane surface is exposed and serves as a cell adhesion receptor to interact with other cell receptors, including PSGL-1 and GPIb. P-selectin upregulates tissue factor in monocytes and leads to leukocyte accumulation in areas of vascular injury associated with thrombosis and inflammation.
Keywords: P-selectin; selectin; PSGL-1; platelet; alpha granule